A Novel Guanine Elicitor Stimulates Immunity in Arabidopsis and Rice by Ethylene and Jasmonic Acid Signaling Pathways - Wang, Lulu; Liu, Haoqi; Yin, Ziyi; Li, Yang; Lu, Chongchong; Wang, Qingbin; Ding, Xinhua (Frontiers in Plant Science, 2022)
Rice sheath blight (ShB) caused by Rhizoctonia solani is one of the most destructive diseases in rice. Fungicides are widely used to control ShB in agriculture. However, decades of excessive traditional fungicide use have led to environmental pollution and increased pathogen resistance. Generally, plant elicitors are regarded as environmentally friendly biological pesticides that enhance plant disease resistance by triggering plant immunity. Previously, we identified that the plant immune inducer ZhiNengCong (ZNC), a crude extract of the endophyte, has high activity and a strong ability to protect plants against pathogens. Here, we further found that guanine, which had a significant effect on inducing plant resistance to pathogens, might be an active component of ZNC. In our study, guanine activated bursts of reactive oxygen species, callose deposition and mitogen-activated protein kinase phosphorylation. Moreover, guanine-induced plant resistance to pathogens depends on ethylene and jasmonic acid but is independent of the salicylic acid signaling pathway. Most importantly, guanine functions as a new plant elicitor with broad-spectrum resistance to activate plant immunity, providing an efficient and environmentally friendly biological elicitor for bacterial and fungal disease biocontrol